SOMATIC LESSONS AS A MEANS OF IMPROVING STUDENTS' PSYCHOPHYSICAL CONDITION. MONITORING OF THE SIXTH DOMAIN MAIA-2ukr (Physical Culture and Sport: Scientific Perspective, 2024)
The materials covered in this article are a continuation of the study of the psychophysical condition of the 1st-year students of higher education. The Multidimensional Assessment of Interoceptive Awareness is an 8-scale questionnaire used by leading experts around the world to study the interoceptive awareness of various population groups. American scientist, PhD Thomas Hanna, conducted the first studies of somatic interoceptive awareness in the United States in the second half of the 20th century.It was determined that after conducting a series of somatic lessons, the participants noted an improvement in their physical and mental state, a decrease in pain in muscles and joints, and the amplitude of movements was minimal. Thanks to the constant awareness of changes in the body, the skill of concentration and maintaining one's emotional balance and self-control was developed/In our country, most people are under constant stress for the last four years. In our case, understanding the situation and maintaining an emotional balance helps to reduce stress, forms a positive background and promotes recovery because the main method of assessment is self-report. All these skills are necessary for all people, including our students - future physical education teachers, coaches, instructors.50 people took part in our research, they are young men and women aged 17-19 years, students of the first year of higher education at the Faculty of Health, Physical Education and Sports of KUBH. In our previous publications, the data of the following scales were made public: "Noticing", "Not-Distracting", "Not-Worrying", "Attention Regulation", "Emotional Awareness" (skill to be aware of emotions). So, the next scale is called "Self-Regulation" (self-regulation skill), according to the version of MAIA-2 (2022).The purpose of the study is to evaluate the "skill of self-regulation" (the sixth domain of interoceptive awareness, Self-Regulation) of first-year students of higher education at the Faculty of Health, Physical Education and Sports.Materials and methods. The following generally accepted methods were used in the article: analysis of scientific and methodological literature and Internet sources, sociological method (MAIA-2ukr survey, sixth domain "6 Self-Regulation: the ability to regulate distress by paying attention to bodily sensations"), methods of mathematical statistics. The level of interoceptive awareness of students of higher education was analyzed using the adapted Ukrainian version of the questionnaire Multidimensional Assessment of Interoceptive Awareness (MAIA-2ukr, https://www.researchgate.net/publication/371450735_MAIA-2_UKR_Original_20220824pdf).
Keywords: interoceptive awareness; somatic education; somatic lessons; somatic movement; somatic movement education; self report